Prevalence and risk factors of postpartum depression in the Middle East: a systematic review and meta-analysis - Hoda Alshikh Ahmad; Asem Alkhatib; Jiayou Luo (BMC, 2021)
Abstract Background Postpartum depression (PPD) is a common social health problem that affects not only the mother and newborn, but extends to other family members as well as various aspects of their lives. This systematic review and meta-analysis aims to identify the prevalence and risk factors of postpartum among the women in Middle East countries. Methods We searched published articles from Web of Science, EMBASE, PubMed and Cochrane electronic databases to establish study articles. Articles regarding postpartum depression prevalence and associated factors among women in the Middle East were included in this systematic review and meta-analysis. A random-effect model was used for estimation of pooled postpartum depression prevalence with a 95% confidence interval (CI) and forest plot. Presence of heterogeneity was checked by Cochran's (Q) test, and funnel plots and Egger's statistical tests were used to assess publication bias. Results A total of 15 studies were included in this systematic review. The studies were conducted in different countries of the Middle East between 2006 and 2020, nine of the included studies were cross-sectional studies and six were cohort studies. The overall pooled estimate of the prevalence of postpartum depression in the Middle East mothers was very high 27% (95% CI 0.19-0.35). The common risk factors reported based on our review were poor economic, pregnancy associated complications, low education, unplanned pregnancy, housewife, inadequate social support from family members and the feeding by formula. Poor economic and complication during pregnancy presented a significant relationship regarding postpartum depression in meta-analysis. Conclusions The prevalence of postpartum depression in the Middle East was higher than other regions of the world. In response to this, we recommend an increase of routine screening for depression during postpartum in this area. Furthermore, it might be necessary to integrate mental health with maternal health care in clinical practice during the postpartum.